Antibacterial activity of phenylboronic acid on pathogenic isolates of Escherichia coli and Staphylococcus aureus - Salman, Halah Dawood; Hammadi, Asmaa H.; Habeeb, Saba Abdulmunem; Dahadh, Ola Abdallah Mahdi (Pharmakeftiki, 2025)
Boron, a bioactive trace element present in humans, plays a critical role in bone formation and maintenance, and exhibits both antibacterial and anti-inflammatory properties. This study investigated the antibacterial activity of boronic acid at varying concentrations in aqueous solution. Phenylboronic acid (PBA) was prepared at concentrations of 3 mg/mL, 6 mg/mL, and 9 mg/mL, and its antibacterial efficacy was assessed using the agar diffusion method against clinically isolated strains of Escherichia coli and Staphylococcus aureus. The results demonstrated a dose-dependent antibacterial effect of PBA on both bacterial species.